REBRANDING DHEA BORDIR SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Putra, Ardi Ghea Satria; Budiardjo, Hardman; Hidayat, Wahyu (Jurnal Art Nouveau, 2016)
Abstract:Dhea Bordir is a fashion company with a product that is focusing in kebaya product either traditional kebaya or contemporary kebaya. Dhea Bordir founded in 1997 by Dewi Asia Arifin in Sidoarjo, East Java. Until 2015 Dhea Bordir still do not have a consistent brand identity that can representing Dhea Bordir product. In conducting promotional activities, Dhea Bordir only depend on mouth-to-mouth promotion. Based on the problem has been discussed, So the formulation problems of research is How to do rebranding Dhea Bordir to increase the brand awareness. The problems that will be discussed in this research was he concept of design and its application in rebranding and promotion media which covering; brand identity, packaging, and Prints promotional media wich including catalogue and brochure and also website promotion.Keywords: Design, Promotion, Communication Visual, Brand Awareness